Hydrochemical characteristics and functions of groundwater in southern Laizhou Bay based on the multivariate statistical analysis approach. (5th March 2021) - Yang, Fan; Liu, Sen; Jia, Chao; Gao, Maosheng; Chang, Wenbo; Wang, Yujue
Abstract: Influenced by paleoclimate, paleogeography and hydrogeology, groundwater with different total dissolved solids (TDS) levels, such as freshwater, brackish water, saline water and brine, widely occurs across southern Laizhou Bay (SLB) . Due to groundwater overexploitation, several groundwater depression cones have gradually formed since the 1970s, resulting in saline water intrusion. In this study, the multivariate statistical analysis (MSA) approach was adopted to identify the hydrochemical characteristics of shallow groundwater (SG) and deep groundwater (DG) in the SLB. Moreover, we applied Gibbs diagrams, hydrochemical facies evolution diagrams (HFE-Diagram) and ion proportion relations to analyze the factors influencing the hydrochemical characteristics. The results showed that hydrochemical zonation of the various water types (ranging from Ca-HCO3 to Na-Cl) from south to north was mainly controlled by migration and mixing of saline water with regional groundwater. Based on the MSA results and hydrochemical characteristics, SG functional areas were divided into the groundwater flow zone, intense groundwater mixing zone and groundwater-seawater interaction zone, and DG functional areas were divided into the groundwater flow zone, groundwater mixing zone and underground brine storage zone. Finally, SG and DG groundwater flow evolution models were developed . The comprehensive method proposed in this study combines the MSA approach with regional geological characteristics and provides a reference for the evaluation of complex multiaquifer systems and analysis of the groundwater evolution characteristics in other regions. Graphical abstract: Image 1 Highlights: Using MSA to identify the hydrochemistry characteristics and evolution processes of SG and DG in SLB. SG function areas are divided into groundwater flow zone, intense groundwater mixing zone and groundwater-seawater interaction zone, and DG function areas are divided into groundwater flow zone, groundwater mixing zone and underground brine storage zone, respectively. Groundwater flow evolution model of SG and DG is summarized.